2009
DOI: 10.1002/rcm.3944
|View full text |Cite
|
Sign up to set email alerts
|

Fast screening and quantitative evaluation of internally deleted goat αs1‐casein variants by mass spectrometric detection of the signature peptides

Abstract: Currently, the internally deleted caprine alphas1-casein (alphas1-CN) variants F and G, associated with low casein expression, are detected by means of ordinary descriptive techniques. No relevant procedure is available to detect internally deleted goat alphas1-CN in bulk milks. The availability of full-length and alphas1-CN F and G variants allowed us to further investigate this issue. Using matrix-assisted laser desorption/ionization time-of-flight (MALDI-TOF) mass spectrometry (MS) and high-performance liqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 25 publications
1
1
0
Order By: Relevance
“…This indicated that the a.a. sequence 59–69 was missing in this sample. Furthermore, the MW value of deleted peptide (f59–69), accounting for 1080 Da, matched exactly the mass difference calculated for B 2 and D 1 variants; the identity of α s1 ‐CN F was confirmed by determination of junction peptides α s1 ‐CN F(f59‐63/43‐63) in the tryptic hydrolysate of the same HPLC peak, consequent to deletion of the sequence (f59–95) from α s1 ‐CN B 2 , as previously found by Picariello et al ; finally, the tryptic peptide map of the third component in the smallest HPLC peak 2 was identical to that of α s1 ‐CN B 2 .…”
Section: Resultssupporting
confidence: 85%
“…This indicated that the a.a. sequence 59–69 was missing in this sample. Furthermore, the MW value of deleted peptide (f59–69), accounting for 1080 Da, matched exactly the mass difference calculated for B 2 and D 1 variants; the identity of α s1 ‐CN F was confirmed by determination of junction peptides α s1 ‐CN F(f59‐63/43‐63) in the tryptic hydrolysate of the same HPLC peak, consequent to deletion of the sequence (f59–95) from α s1 ‐CN B 2 , as previously found by Picariello et al ; finally, the tryptic peptide map of the third component in the smallest HPLC peak 2 was identical to that of α s1 ‐CN B 2 .…”
Section: Resultssupporting
confidence: 85%
“…4,7 These values are above those of other common nonimmunoassay protein detection methods, for example, polyacrylamide gel electrophoresis (PAGE) with silver staining (∼30À 200 fmol), 18 multiple reaction monitoring (MRM) (10À50 amol), 19 or bottom-up protocols such as peptide mass fingerprinting (0.5À5 fmol). 20,21 The sensitivities of the previous online LC/MS top-down platforms were limited by relatively poor RPLC peak resolution, with reported peak widths at half max (w h ) of 17À60 s. These peak widths far exceed the temporal resolution of individual MS scan events (typically 0.1À1.5 s) with detrimental effects on experimental LOD and peak capacity.…”
Section: ' Results and Discussionmentioning
confidence: 99%